Supporting the survivors: experiences and perceptions of peer support offered to UK terrorist survivors - Rew, Nichola Emma Jalfon (International review of victimology, 2021)
Recent terror incidents in the UK, including the targeting of concert attendees in Manchester, to individuals socialising and working in central London, highlight the public’s vulnerability and that attacks can be indiscriminate, resulting in any individual becoming a victim to this fearful crime. As a consequence of these and other attacks, including those overseas, media reporting within the UK has increasingly focused on the inadequate levels of support offered to survivors from official agencies. However, little evaluation has been conducted regarding the benefits of support networks and online support groups created directly by those individuals affected by terror attacks., Quantitative research findings obtained through a self-administered online questionnaire, completed by 81 survivors of terrorist attacks who are members of different peer support networks in the UK, endorsed that while victims feel that adequate professional support is lacking, significant positive experiences have been achieved through peer support, particularly through the internet. This first independent academic study found that it was these methods of support that had the most resonance with individuals and offers several recommendations, based on findings, which could enhance and improve support for survivors of terrorism in the future.